2019
DOI: 10.1002/pmic.201900175
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Treated Roots of Oryza australiensis Seedlings are Enriched with Proteins Involved in Energetics and Transport

Abstract: Salinity is a major constraint on rice productivity worldwide. However, mechanisms of salt tolerance in wild rice relatives are unknown. Root microsomal proteins are extracted from two Oryza australiensis accessions contrasting in salt tolerance. Whole roots of 2‐week‐old seedlings are treated with 80 mM NaCl for 30 days to induce salt stress. Proteins are quantified by tandem mass tags (TMT) and triple‐stage Mass Spectrometry. More than 200 differentially expressed proteins between the salt‐treated and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Increasing soluble sugar content in plant tissues is often reported alongside reductions in starch reserves as stored carbohydrates are mobilised, requiring the expression of a suite of genes involved in starch degradation and monosaccharide transport (Kaplan et al 2006 ). For example, Yichie et al ( 2019 ) reported increases in expression of a starch synthase in a salt-susceptible population of wild rice, while a tolerant population of the same species had increased expression of monosaccharide transporters. The rapid slowing of biomass accumulation in O. sativa after 28 days at 45 °C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing soluble sugar content in plant tissues is often reported alongside reductions in starch reserves as stored carbohydrates are mobilised, requiring the expression of a suite of genes involved in starch degradation and monosaccharide transport (Kaplan et al 2006 ). For example, Yichie et al ( 2019 ) reported increases in expression of a starch synthase in a salt-susceptible population of wild rice, while a tolerant population of the same species had increased expression of monosaccharide transporters. The rapid slowing of biomass accumulation in O. sativa after 28 days at 45 °C (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity tolerance in rice is a quantitative trait that involves a complex of physiological responses, metabolic processes, and gene expression networks [47,48]. A previous study reported that salt tolerance in O. australiensis, exposure to 80 mM NaCl, resulted in a high response of proteins that belong to the transport, metabolic process, and transmembrane transporter categories [49]. In this study, we found that O. australiensis wild rice accession JC 2304 exhibited tolerance to 150 mM NaCl by rapidly accumulating free proline, lowering osmotic potential, maintaining high RWC, high membrane integrity, and low Na + in the shoots and roots.…”
Section: Discussionmentioning
confidence: 99%
“…It is The copyright holder for this preprint this version posted May 25, 2021. ; https://doi.org/10.1101/2021.05.24.445367 doi: bioRxiv preprint defence against ROS (Zhu et al, 2020). Increased abundance of ATP synthase subunits was reported in salt stressed barley and rice roots (Zhu et al, 2020;Yichie et al, 2019;Liu et al, 2014), however in our study ATP synthase subunits were decreased in abundance in root tips (Fig. 5, Fig.…”
Section: Discussionmentioning
confidence: 45%